The analysis on the seismic behavior of L-shaped prefabricated special-shaped CFST with rectangular multi-cell columns. Issue 8 (June 2022) - Wang, Lai; Cui, Wenbin; Liu, Su; Chen, Huirong; Chen, Haitao
In this paper, a prefabricated special-shaped concrete-filled steel tube (CFST) with rectangular multi-cell column has been subjected to low cyclic reversed loading experiment and finite element (FE) parameter analysis. A total of three full-scale L-shaped specimens were tested under constant axial compression load and transverse cyclic load. The main variable in the experiment was the direction of loading. The results show that the failure mode of the special-shaped column specimen is compression-bending failure. Within 300 mm of the bottom of the column, the steel tube bulges or even cracks, the concrete powder fells and fails to exit the work. Among them, the L-135° specimen has the highest peak bearing capacity while the L-0° specimen has better ductility. The main variables of FE parametric analysis are axial compression ratio, concrete grade, steel tube thickness and loading angle. The analysis results show that the lower axial compression ratio and higher concrete grade are conducive to the improvement of bearing capacity. As the thickness of the steel tube increases, the peak bearing capacity and displacement of the specimen increases but the ductility decreases. The special-shaped column model has better seismic behavior when loaded along various loading angles. The peak bearing capacity of the special-shaped column specimen loaded at 135° is consistent with the test results and compared with the L-45° specimen, its bearing capacity is increased by up to 62.04%, which has better comprehensive seismic behavior.